2007
DOI: 10.1007/s10551-007-9383-7
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility, Investor Protection, and Earnings Management: Some International Evidence

Abstract: G21, G34, G38, M41, corporate governance, corporate social responsibility (CSR), earnings management, earnings opacity, investor protection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
548
12
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(659 citation statements)
references
References 42 publications
(35 reference statements)
75
548
12
24
Order By: Relevance
“…Previous studies suggested that the above firm-specific characteristics are useful to predict earnings management (Kim et al 2012;Hong and Andersen 2011;Chih et al 2008). SIZE is included in the regression to control for the potintal impact of firm size on the earnings management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the above firm-specific characteristics are useful to predict earnings management (Kim et al 2012;Hong and Andersen 2011;Chih et al 2008). SIZE is included in the regression to control for the potintal impact of firm size on the earnings management.…”
Section: Methodsmentioning
confidence: 99%
“…GSALES and MB are included to control for a firm growth. It is expected that firms with high growth tend to manage discretionary accruals upwards due to they are under the greatest pressure to adopt aggressive accounting policies to report increased earnings (Chih et al 2008). Loss is included to control for financial condition of the firm and expected that firms that faced financial problems tend to engage in income-decreasing earnings management (Healy 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian ini juga berkontribusi untuk menjelaskan berbagai pelanggaran etika bisnis dengan menggunakan aktivitas CSR sebagai kedok penutup (Chih et al., 2008;Hong dan Andersen, 2011). Sebagai contoh, perusahaan Enron yang melakukan skandal manipulasi laba terbesar dalam sejarah Amerika Serikat pada tahun 2000 ternyata melakukan aktivitas CSR secara intensif (Kim et al., 2012).…”
Section: Pendahuluanunclassified
“…CSR disclosure commitment is a means of shaping a firm's public image and legitimacy [8], but it may also be used to divert attention from unethical practices through social performance communication. Accordingly, Chih et al [9] point out examples of internationally-known large scale companies-i.e., Shell, Coca Cola and British American Tobacco-strongly committed to the disclosure of their CSR activities, while at the same time, not behaving in a socially responsible manner. Enron, a well-known case, was very active in publishing social and environmental reports on its responsible work, while it was engaging in false financial information.…”
Section: Introductionmentioning
confidence: 99%